Modeling and Simulation of Induction Motor based on Finite Element Analysis - Yemna Bensalem; Mohamed Naceur Abdelkrim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper presents the development of a co-simulation platform of induction motor (IM). For the simulation, a coupled model is introduced which contains the control, the power electronics and also the induction machine. Each of these components is simulated in different software environments. So, this study provides an advanced modeling and simulation tools for IM which integrate all the components into one common simulation platform environment. In this work, the IM is created using Ansys-Maxwell based on Finite Element Analysis (FEA), whereas the power electronic converter is developed in Ansys-Simplorer and the control scheme is build in MATLAB-Simulink environment. Such structure can be useful for accurate design and allows coupling analysis for more realistic simulation. This platform is exploited to analyze the system models with faults caused by failures of different drive’s components. Here, two studies cases are presented: the first is the effects of a faulty device of the PWM inverter, and the second case is the influence of the short circuit of two stator phases. In order to study the performance of the control drive of the IM under fault conditions, a co-simulation of the global dynamic model has been proposed to analyze the IM behavior and control drives. In this work, the co-simulation has been performed; furthermore the simulation results of scalar control allowed verifying the precision of the proposed FEM platform.